2020
DOI: 10.1371/journal.pone.0241859
|View full text |Cite
|
Sign up to set email alerts
|

Soil C, N, P and K stoichiometry affected by vegetation restoration patterns in the alpine region of the Loess Plateau, Northwest China

Abstract: The Grain-for-Green project is an important ecological restoration measure to address the degradation of alpine ecosystems in China, which has an important impact on the ecological stoichiometry of soil carbon (C), nitrogen (N), phosphorus (P) and potassium (K). However, soil stoichiometry changes under different vegetation restoration patterns and at different soil depths remain poorly understood in the alpine region of the Loess Plateau. To clarify these soil stoichiometry changes, a 0–60 cm soil profile was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
9
1
Order By: Relevance
“…Similar results had been obtained for the Yellow River Wetland in Baotou [19], Horqin Sandy Land [24], and Chongqing Mountain [57]. In this study, soil pH was only significantly correlated with R NP , R NK , and R PK , which was inconsistent with the research conducted in paddy fields [58] and in the alpine region of the Loess Plateau [59]; however, fertilization caused soil stoichiometry in farmland to be greatly affected by soil pH [60]. This may be related to the land type, geographical environment, and research scale in the study area, so that the conclusions drawn have regional limitations.…”
Section: Effects Of Environmental Factors On the Eco-stoichiometry Of...contrasting
confidence: 53%
“…Similar results had been obtained for the Yellow River Wetland in Baotou [19], Horqin Sandy Land [24], and Chongqing Mountain [57]. In this study, soil pH was only significantly correlated with R NP , R NK , and R PK , which was inconsistent with the research conducted in paddy fields [58] and in the alpine region of the Loess Plateau [59]; however, fertilization caused soil stoichiometry in farmland to be greatly affected by soil pH [60]. This may be related to the land type, geographical environment, and research scale in the study area, so that the conclusions drawn have regional limitations.…”
Section: Effects Of Environmental Factors On the Eco-stoichiometry Of...contrasting
confidence: 53%
“…Soil nutrients differ significantly across land-use types. , and Liu and Wang., 2020, for example, investigated alpine regions such as the Qinghai-Tibet Plateau and the Loess Plateau and discovered that C and N contents, C:P, and N:P were higher in forestland than in grassland and farmland, and pH was lower in forestland than in grassland and farmland [15,16]. Liu et al, 2017, found that P content, C:N, C:P, and N:P were lower in grassland soils of the Yili River Valley in Xinjiang than in shrubland soils [17].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the P content in leaves and roots of H. ammodendron , there was no significant correlation between soil N:P and N, P ecological stoichiometry in different organs of H. ammodendron , indicating that soil nutrient stoichiometry had little direct effect on the organs of H. ammodendron , which may be due to the fact thatH. ammodendron was limited by both water and nutrient elements, and formed unique ecological stoichiometry and physiological and ecological habits after long-term evolution (Liu & Wang, 2020). Soil pH affects the solubility of mineral salts, which in turn affects the effectiveness of soil nutrients (Bell et al, 2014).…”
Section: H Ammodendronmentioning
confidence: 91%